THE ROLE OF ADVERTISING TAX THROUGH MEASURING THEIR EFFECTIVENESS, GROWTH AND CONTRIBUTION TO LOCAL TAXES IN LUMAJANG REGENCY - Galih Wicaksono (Institute of Computer Science (IOCS), 2022)
Advertising tax is one type of local tax that is well known by the public, given its reach at several strategic points that can be seen by the public. The purpose of this study was to determine the effectiveness, growth, and contribution of the advertisement tax to local taxes in Lumajang Regency for the 2018-2020 period. The type of research is descriptive quantitative, the source of data is from the Regional Tax and Retribution Agency of Lumajang Regency, previous research and the internet, as well as data analysis techniques using the calculation of the effectiveness, growth, and contribution of advertisement tax to local taxes. The results of this study are the effectiveness is in the very effective position, the growth is in a volatile position, and the contribution to local taxes is in the very less category.